Efficacy of leuprolide acetate versus triptorelin pamoate administered every 3 months for treatment of central precocious puberty - Thanaporn Thaneetrakool; Suphab Aroonparkmongkol; Nattakarn Numsriskulrat; Vichit Supornsilchai; Suttipong Wacharasindhu; Khomsak Srilanchakon (Clinical and Experimental Pediatrics)
Background Central precocious puberty (CPP) is typically treated with gonadotropin-releasing hormone (GnRH) agonists. Although numerous GnRH agonist variants are available, limited research has compared the efficacy of leuprolide acetate and triptorelin pamoate administered at 3-month intervals. Purpose This study aimed to assess the efficacy of CPP treatment with triptorelin pamoate and leuprolide acetate administered at 3-month intervals. Methods This retrospective cohort study included 116 girls with CPP: 71 treated with leuprolide acetate every 3 months and 45 treated with triptorelin pamoate every 3 months. Anthropometric measurements were compared before and after therapy. At 6 months after the therapy, luteinizing hormone (LH) suppression was evaluated. Results When administered every 3 months, leuprolide acetate and triptorelin pamoate significantly suppressed LH. The predicted adult height (PAH) and degree of bone age advancement at the end of treatment were comparable. Conclusion Treatment with leuprolide acetate and triptorelin pamoate every 3 months did not have significantly different effects on LH suppression or PAH.